Comparison between active and passive biomonitoring strategies for the assessment of genotoxicity and metal bioaccumulation in Echinogammarus veneris (Crustacea: Amphipoda). Issue 2 (2nd April 2016) - Ronci, L.; Meccoli, L.; Iannilli, V.; Menegoni, P.; De Matthaeis, E.; Setini, A.
Abstract: The aim of this study was to investigate the relevance and the robustness of active and passive approaches used in freshwater biomonitoring with the ecologically relevant gammarid amphipod Echinogammarus veneris . To assess the contaminant bioavailability in two rivers of Latium (Central Italy), we measured the genotoxic potential in haemocytes by comet assay and metal bioaccumulation in tissues by analytical methods. We adopted an active strategy of exposure in situ and a passive method of sampling in situ . In the first case, the gammarids were exposed in cages in several sampling sites selected along two rivers, while in the sampling in situ, individuals were collected directly in the same sampling sites and then analyzed. The results indicate that the comet assay carried out on haemocytes from caged individuals proved to be a sensitive tool for freshwater genotoxicity monitoring. However, the sampling in situ is more appropriate for a realistic understanding of the presence of trace metal in E. veneris .